2001
DOI: 10.1254/jjp.87.189
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Affinity and Dissociation Ability of a Newly Synthesized 5-HT2 Antagonist, AT-1015: Comparison With Other 5-HT2 Antagonists

Abstract: ABSTRACT-This study investigated the binding affinities of a newly synthesized 5-HT2 antagonist, AT-1015 (N-[2-[4-(5H-dibenzo[a,d]cyclohepten-5-ylidene)-piperidino]ethyl]-1-formyl-4-piperidinecarboxamide monohydrochloride monohydrate) for [3 H]ketanserin bindings to 5-HT2 receptors in the rabbit cerebral cortex membranes using the radioligand binding assay method. The affinity of this compound was also compared with other 5-HT2-selective antagonists such as ketanserin, sarpogrelate, cyproheptadine and ritanser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In addition, cyproheptadine caused an increase in delta activity during non-REM sleep, indicating that this drug showed sleep qualityenhancement effects. Different from diphenhydramine and chlorpheniramine, cyproheptadine is well known to have a potent anti-serotonergic effect through 5-HT 2 receptors besides an anti-histaminergic effect (26). Viola et al (27) and Kantor et al (28) reported that ritanserin, a 5-HT 2 -receptor antagonist, induced an increase in slow-wave sleep, REM sleep, and delta activity in poor sleepers and rats.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cyproheptadine caused an increase in delta activity during non-REM sleep, indicating that this drug showed sleep qualityenhancement effects. Different from diphenhydramine and chlorpheniramine, cyproheptadine is well known to have a potent anti-serotonergic effect through 5-HT 2 receptors besides an anti-histaminergic effect (26). Viola et al (27) and Kantor et al (28) reported that ritanserin, a 5-HT 2 -receptor antagonist, induced an increase in slow-wave sleep, REM sleep, and delta activity in poor sleepers and rats.…”
Section: Discussionmentioning
confidence: 99%
“…Other 5HT 2A receptor antagonists have been available in the past that also showed ef icacy in acute arterial thrombosis, e.g., ketanserin [26] ritanserin [9], LU 49938 [27], MDL11,939, and LY53,857 [21], MDL 28,133A [28], DV-7028 [29], AT-1015 [30,31], APD791 [32][33][34]. The 5HT 2A antagonists presently available are Th001 (Arteclere TM ), a speci ic platelet receptor antagonist and nefazodone [35], an antidepressant now taken off the market with non-platelet effects and an unknown effect on thrombosis.…”
Section: Serotonin Dependence Of Acute Arterial Thrombosis and Its Inmentioning
confidence: 99%
“…Radioligand binding assay to quantify muscarinic receptor occupation was performed as described previously [26,29] with minor modifications. All binding assays were initiated by adding 50 ll (0.25 mg/ml or 50 lg/assay) of crude membrane to samples on ice containing a final volume of 200 ll of assay buffer (60 mM Tris-HCl, 20 mM MgCl 2 , and 0.1% ascorbic acid), varying concentrations of Nonspecific binding was determined in the presence of nonlabeled At sulfate, 0.1 mM.…”
Section: Radioligand Binding Assaymentioning
confidence: 99%